2014
DOI: 10.1371/journal.pone.0090675
|View full text |Cite
|
Sign up to set email alerts
|

Purine Analog-Like Properties of Bendamustine Underlie Rapid Activation of DNA Damage Response and Synergistic Effects with Pyrimidine Analogues in Lymphoid Malignancies

Abstract: Bendamustine has shown considerable clinical activity against indolent lymphoid malignancies as a single agent or in combination with rituximab, but combination with additional anti-cancer drugs may be required for refractory and/or relapsed cases as well as other intractable tumors. In this study, we attempted to determine suitable anti-cancer drugs to be combined with bendamustine for the treatment of mantle cell lymphoma, diffuse large B-cell lymphoma, aggressive lymphomas and multiple myeloma, all of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…A very recent study on several hematologic malignancies revealed IC 50 values between approximately 10 μM and 250 μM. Especially mantle cell lymphoma, Burkitt’s lymphoma and T-cell acute lymphoblastic leukemia derived cell lines were relatively sensitive to bendamustine treatment [ 50 ]. The IC 50 value (approximately 50 μM) reported by Hiraoka et al [ 50 ] for Jurkat cells is in good agreement with our data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent study on several hematologic malignancies revealed IC 50 values between approximately 10 μM and 250 μM. Especially mantle cell lymphoma, Burkitt’s lymphoma and T-cell acute lymphoblastic leukemia derived cell lines were relatively sensitive to bendamustine treatment [ 50 ]. The IC 50 value (approximately 50 μM) reported by Hiraoka et al [ 50 ] for Jurkat cells is in good agreement with our data.…”
Section: Resultsmentioning
confidence: 99%
“…Especially mantle cell lymphoma, Burkitt’s lymphoma and T-cell acute lymphoblastic leukemia derived cell lines were relatively sensitive to bendamustine treatment [ 50 ]. The IC 50 value (approximately 50 μM) reported by Hiraoka et al [ 50 ] for Jurkat cells is in good agreement with our data. Published plasma levels of 1 after intravenous administration (C max = 6 μg/mL (≈ 17 μM) [ 51 ]; C max = 11 μg/mL (≈ 31 μM) [ 52 ]) suggest that the chemotherapy with bendamustine must be considered ineffective in case of tumor entities showing IC 50 values in the two- to three-digit micromolar range in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that NL-101-induced cell cycle arrest at different stages is possibly due to its "alkylation activity," exhibiting similar concentration-dependent properties as bendamustine. Indeed, a considerable part of research has found that bendamustine alone can induce S phase arrest in different cell lines due to inducing DNA strand breaks [15,42]. Moreover, Beeharry et al found that in a wide panel of cancer cell lines, bendamustine presented concentrationdependent effects on cell cycle checkpoint [33].…”
Section: Discussionmentioning
confidence: 99%
“…Bendamustine belongs to the alkylating agent class of cytotoxic drugs. It contains a nitrogen mustard group responsible for alkylating activity (Gandhi & Burger, ) and, potentially, purine analogue‐like properties which may be responsible for the rapid onset of action and unique synergistic capabilities (Hiraoka et al , ), although this is somewhat controversial (Gandhi & Burger, ). The lymphodepleting capabilities of alkylator agents including bendamustine are well recognised (Kufe et al , ).…”
mentioning
confidence: 99%